INTERNALIZATION OF EDUCATIONAL VALUES THROUGH RELIGIOUS EXTRACURRICULARS IN BODEH STATE JUNIOR HIGH SCHOOL, PEMALANG DISTRICT - Ma'ruf, Amar; Tazali, Imam; Suryani, Ery; Lidwan , Nanang; Abror, Dzulchan (Jurnal Konseling Pendidikan Islam, 2023)
This article aims to discuss the internalization of educational moral values ​​through religious extracurricular activities at SMP N 1 Bodeh for all. This study aims to analyze religious extracurricular activities at SMP N 1 Bodeh about educational moral values, to examine the strategies adopted in internalizing educational moral values ​​through religious extracurricular activities at SMP N 1 Bodeh, to investigate the implications of internalizing educational moral values ​​through religious extracurricular at SMP N 1 Bodeh.? The type of research was field research. The method used a qualitative. The findings of this study indicate that religious extracurriculars related to educational moral values ​​are the customs such as reading an asmaul husna, dhuha prayer, zuhr prayer, tahfidzul Qur'an ( tajweed, makharij al letters, imla' and memorizing the Qur'an) , the practice of tambourine keys, and studying scriptures (aqidatul lay, syu'aibul faith, akhlaqul banin), speeches and other activities such as mawlid al-nabi, pilgrimage, and other activities . The internalization strategy of educational moral values ​​through religious extracurriculars at SMP N 1 Bodeh, namely giving good advice through lectures, setting good examples, habituation, commemorating Islamic holidays, teaching about morals from the book of akhlakul ban in, aqidatul lay and syu 'abul faith. The internalization implications of the educational moral values ​​through religious extracurricular at SMP N 1 Bodeh are increased discipline, good morals, positive habits, increase in worship, and championships in the religious field.